2023
DOI: 10.4103/sja.sja_654_22
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthetic management of a patient with Gerbode defect

Abstract: Gerbode defect is a rare left ventricle to right atrium shunt that can be acquired or congenital. The incidence of acquired defects has been growing and is caused by previous cardiac surgery, endocarditis, trauma and myocardial infarct. It can be challenging and the anesthesiologist should maintain a suspicion when there is circulatory failure after a cardiac surgery. It can be diagnosed by trans-esophageal echocardiography. In this case we presented the anesthetic management and the successful surgical correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…In addition, the increased right ventricular preload causes pulmonary circulation overload with a subsequent volume loading and enlargement of the left heart cavities [ 1 , 33 , 38 ]. Thus, in the case of a significant shunt with therapeutic delay, the acyanotic Gerbode defect [ 44 ] may result in dilatation of all cardiac cavities, pulmonary artery hypertension and congestion, as well as low cardiac output and a decline in global cardiac function [ 11 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In addition, the increased right ventricular preload causes pulmonary circulation overload with a subsequent volume loading and enlargement of the left heart cavities [ 1 , 33 , 38 ]. Thus, in the case of a significant shunt with therapeutic delay, the acyanotic Gerbode defect [ 44 ] may result in dilatation of all cardiac cavities, pulmonary artery hypertension and congestion, as well as low cardiac output and a decline in global cardiac function [ 11 , 50 ].…”
Section: Resultsmentioning
confidence: 99%
“…The extent of symptomatology depends on the size of the defect and the volume and duration of the LV-RA shunt [ 7 , 12 ]. The systematic literature review by Yuan [ 5 ] reported that more than 25% of patients suffering from the congenital Gerbode defect were asymptomatic in the context of incidental findings, whereas dyspnea, systolic heart failure, and fever accounted for the prevalent clinical manifestations [ 50 ]. Dyspnea is caused by pulmonary arterial hypertension with congestion.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations